Lipohypertrophy due to HAART: a case series - Rao, Arikeri Vasu Deva; Reddy L., Samarasimha; Velupula, Srinivas; N., Jayababu; Khan, Imran; Kumar M., Kiran (International Journal of Basic & Clinical Pharmacology, 2018)
A subset of HIV-1 infected patients undergoing Highly Active Antiretroviral Therapy (HAART) develops a lipodystrophy syndrome. It is characterised by loss of subcutaneous adipose tissue (face, limbs and buttocks) visceral fat accumulation and lipomatosis especially in dorsocervical area. In addition these patients show metabolic alteration implicative of metabolic syndrome particularly dyslipidaemia and insulin resistance. These alterations lead to enhanced cardiovascular risk and favour the development of diabetes in such patients. A complex combination of HIV infection, drug treatment related events and lipotoxicity appears to contribute to the development of lipodystrophy syndrome. Active lipolysis in subcutaneous fat combined with impaired storage capacity in subcutaneous depot leads to ectopic deposition of lipids either in visceral or in non-adipose sites. Lipotoxicity, a pathogenic factor in the lipodystrophy syndrome should be considered in the strategies for treating and /or preventing the morphological alterations and systemic metabolic disturbances associated with lipodystrophy.